Guidelines for evaluating process plant buildings for external explosions and fires. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1996)
Dedicated to the Memory and Spirit of Donald F. Othmer Though there are many industry practices for building design and siting, they do not always apply to all sectors of the industry, or ensure consistent levels of safety. This practical book, written by the same author as API Recommended Practice 752, provides the details to implement the recommended practice, "Management of Hazards Associated with Location of Process Plant Buildings." Its contents include safety guidelines on fire and explosion risks to process plant buildings as a result of events external to the building, which.
Keywords: Chemical plants -- Fires and fire prevention.; Explosions.; Chemical plants -- Risk assessment.; Risk management.; elektronické knihy; electronic books